Empowering mothers, enhancing English: A family-centered community-based intervention for primary EFL learners - Fitri Yulianti; Bodbaeva Cholpon Beishekeevna; Dinara Asanova (Scientific English, 2026)
This study investigates the effectiveness of a community-based English coaching program for mothers, named English Mommies Club, in improving both maternal English competency and primary students’ English acquisition. The participants were 30 mothers of primary school learners and their 30 children, enrolled in Grades 4 to 6 at state and private primary schools in Indonesia, representing diverse educational backgrounds and family contexts. Grounded in the premise that parents, particularly mothers, play a central role in children’s academic development, the study employed a dominant quantitative experimental design with a supportive qualitative component. Pre- and post-tests were administered to both mothers and students to measure changes in English proficiency, while questionnaires were distributed to capture shifts in parental involvement and learning behaviors. The findings indicate significant improvements in mothers’ English competency following participation in the program, accompanied by measurable gains in students’ English performance. A positive relationship was also identified between maternal English proficiency and students’ English acquisition. Overall, the study highlights the importance of empowering mothers linguistically as a strategic approach to strengthening English learning outcomes in primary education contexts.